The Role of Family in Mitigating Youth Social Violence from an Islamic Perspective - Ushama, Thameem; Uddin, Helal; Arkam, Mohamed (Advances in Social Sciences Research Journal, 2024)
This study examines within an Islamic framework while examining families’ vital role in preventing societal violence among young people. In Islam, parents are the primary instructors, and the child’s first school is the home. The research explores how families could stop the growth in juvenile social violence by looking at Islamic viewpoints on family structure, values, and teachings. Analytical and descriptive methods are used in this investigation. It explores the potential role of families as essential building blocks in fostering responsible and peaceful behaviour in the youths, highlighting the significance of family dynamics and values. It looks at how important it is to instil Islamic morals and social skills in the family to foster a feeling of belonging, compassion, and defiance of violent impulses. It offers a profound understanding of how families could function as preventative and corrective measures against social violence by fusing Islamic teachings with contemporary perspectives. The study’s conclusions provide light on the relationship between Islamic principles, family dynamics, and the prevention of social violence. These insights can be used in debates and real-world community well-being initiatives.